2020
DOI: 10.1088/1361-6641/ab7773
|View full text |Cite
|
Sign up to set email alerts
|

Study on the effect of diamond layer on the performance of double-channel AlGaN/GaN HEMTs

Abstract: The thermal effect is an important reliability issue for GaN-based devices. The impact of the diamond layer on double-channel AlGaN/GaN HEMTs (DC-HEMTs) is first investigated in this paper by Sentaurus TCAD simulation. By utilizing the diamond layer, the lattice temperature along the channel can be modulated and becomes more even. The results show that the peak lattice temperature can be reduced by 64 K when the power dissipation increases to 46 W mm −1 in the DC-HEMT with a diamond layer. A 1 μm thick diamond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The impact of capping double-channel HEMTs was also evaluated with thermo-electrical simulations [157]. The authors observed that the PCD layer provides a lateral heat conduction path close to the hot spot located at near the drain side of the gate edge, modulating the channel lattice temperature distribution and making it become more uniform.…”
Section: Capping Diamondmentioning
confidence: 99%
“…The impact of capping double-channel HEMTs was also evaluated with thermo-electrical simulations [157]. The authors observed that the PCD layer provides a lateral heat conduction path close to the hot spot located at near the drain side of the gate edge, modulating the channel lattice temperature distribution and making it become more uniform.…”
Section: Capping Diamondmentioning
confidence: 99%
“…Semiconductor devices will generate heat during normal operation, especially HEMTs composed of third-generation wide-gap semiconductor material with the high output power density and high-frequency characteristics. The increase in temperature will cause performance degradation and even unrecoverable damage to the device [8,19,36], which contributes to an obvious gap between actual performance and theoretical performance of HEMTs. Therefore, in order to improve the working efficiency of HEMTs, the temperature rise phenomenon needs to be studied emphatically.…”
Section: Thermal Characteristicsmentioning
confidence: 99%
“…A. Jarndal et al developed a large-signal model of GaN HMET, which takes into account the performance degradation caused by temperature rise and can accurately predict self-heating-induced current dispersion [18]. T. Zhu et al plated a diamond layer above the passivation layer for GaN HEMT, which can improve heat dissipation [19]. Due to its military value, the study of HPM effects has also become a hot spot in recent decades.…”
Section: Introductionmentioning
confidence: 99%
“…[12] The implementation of DC-GaN-HEMTs substantially obtains higher power gain capability and cutoff frequency than SC devices, which are of great significances in terms of RF circuit designs. [13,14] Furthermore, DC-GaN-HEMTs are potential devices for radiation sensors due to an improvement of the heavy ion sensitivity and the proper switching ability by introducing a dual gate. [15] Enhancement-mode DC-GaN-HEMTs by the fully recessed gate at the barrier layer complemented with the superior mobility have also attracted much attention, and the parasitic channel exhibits high mobilities since the spatial separation from the etched interface.…”
Section: Introductionmentioning
confidence: 99%